Effective charge and energy transfers within a metal–organic framework for efficient photocatalytic oxidation of amines and sulfides. Issue 39 (15th September 2022) - Wang, Shao-Dan; Lai, Chun-Lin; Zhang, Yi-Xuan; Bao, Shu-Tong; Lv, Kang-Le; Wen, Li-Li
Abstract : Visible-light-responsive CCNU-16 exhibited excellent activity toward photocatalytic oxidation of amines and sulfides under ambient conditions, which was attributed to the combination of synergistic charge transfer and energy transfer processes. Abstract : The photocatalytic reaction is regarded as an efficient and sustainable strategy to convert solar energy into chemical energy. In the work, a novel metal–organic framework Zn5 (TPyP)(BCTC)2 (H2 O)3 (denoted as CCNU-16, H2 TPyP = 5, 10, 15, 20-tetra(4-pyridyl)-21 H, 23 H -porphine, H4 BCTC = [9, 9′-bicarbazole]-3, 3′, 6, 6′-tetracarboxylic acid) was successfully synthesized from porphyrin- and carbazole-based organic linkers, which exhibits excellent visible-light-responsive characteristic. CCNU-16 was further applied toward photo-induced aerobic oxidation of amines and sulfides in air under visible light illumination and ambient conditions. Outstandingly, the turnover frequency (TOF) of the photocatalytic oxidative coupling of benzylamine over CCNU-16 is at the high end among MOF-based photocatalysts, so far, even under green and mild conditions. The excellent photocatalytic activity is attributed to superoxide radical anion (O2 ˙ − ) and singlet oxygen ( 1 O2 ) generated by the synergistic charge transfer (CT) and energy transfer (ET) processes, which provide a reasonable and efficient method for the photocatalytic oxidation of organic transformations.